How the Holocaust Looks Now
XXXIX, 282 p.
Keywords: This collection offers a series of essays that explore the historical culture the holocaust has engendered in Europe, Israel and the USA, the politics of its reception and representation, the motivations for and effectiveness of commemorating it, and the creative and didactic practices it has generated in contemporary literature, art, and thought.